Brave, not perfect : fear less, fail more, and live bolder - Saujani, Reshma (Currency, 2019)
"New York Times bestselling author and Girls Who Code founder/CEO Reshma Saujani inspires us to discover the power of female bravery. Do you ever feel crushed under the weight of your own expectations? Do you often lose sleep ruminating over a tiny mistake or worrying about what someone else thinks of you? Do you run yourself ragged trying to do it all at home and at work, with a smile and not a hair out of place? Have you ever passed up an opportunity--a new relationship, new job, or new challenge--because you're afraid you won't immediately excel at it? For you, is failure simply not an option? You're not alone. As women, we've been taught from an early age to play it safe. Well-meaning parents and teachers rewarded us for being quiet and polite, urged us to be careful so we don't get hurt, and steered us to activities at which we could shine. Meanwhile, boys were expected to speak up, get dirty, play rough, and climb to the top of the monkey bars. In short, boys are taught to be brave, while girls are taught to be perfect. As a result, we grow up to be women who are afraid to fail. So terrified of not doing everything perfectly, we tamp down our dreams and narrow our world, along with our opportunities for happiness. As too many of us eventually learn, being afraid to take risks, to use our voice to take a stand or ask for what we want, even to make mistakes, leads to a lot of disappointment and regret. But it doesn't have to be this way. In a book inspired by her hugely popular TED Talk, Reshma Saujani shows us how to end our love affair with perfection and rewire ourselves for bravery. Drawing on hundreds of interviews with girls and women from around the country, stories of women changing the world one brave act at a time, and her own personal journey, Saujani shares an array of powerful insights and practices to make bravery a lifelong habit and enable us to be the authors of our biggest, boldest, and most joyful life"--